Assessing the Role of Collective Efficacy Beliefs During Participative Occupational Health Interventions - Kuchenbaur, Marco; Peter, Richard (Frontiers in Public Health, 2021)
Background: For group-based participatory interventions in the context of occupational health, no questionnaires exist to assess the participants’ active engagement in the interventions. On the basis of the construct of collective efficacy beliefs, this study has developed a questionnaire with which the group-related efficacy beliefs can be assessed as a precondition for participants actively engaging in participative interventions. Methods: Participants were drawn from a two-arm cluster-randomized intervention study to fill out the questionnaire. A Factor analysis and an initial psychometric calibration were performed. In a second step, the group-related properties of the questionnaire were validated using a Multilevel analysis. Results: The factorial structure of the questionnaire is consistent with the theory of efficacy beliefs according to A. Bandura. Furthermore, the collective efficacy expectations of the interventions participants are lowered in the absence of appreciation and support in the psychosocial environment of the worksite. Conclusions: Assessing participant’s quality of interventional activity in participatory interventions by collective efficacy can be valuable in understanding the amount of interventional activity. In addition, it is recommended to consider the influence of the worksite’s psychosocial environment on collective efficacy beliefs when implementing participatory interventions. Trial registration: Registration trial DRKS00021138 on the German Registry of Clinical Studies (DRKS), retrospectively registered on 25 March, 2020.